AB0029 Anti inflammatory effect of pde5 inhibition: scope for a new potential indication in ssc associated myositis. (15th June 2017) - Corinaldesi, C; Abignano, G; Antinozzi, C; Riccieri, V; Valesini, G; Vasile, M; Marampon, F; Lenzi, A; Ballard, K; Galdo, F Del; Crescioli, C
Abstract : Background: Skeletal muscle damage can occur as clinical manifestation of Systemic Sclerosis (SSc) [1], and it is known to be associated to type I IFN pathway activation [2]. The type I IFN-induced chemokine CXCL10 is associated with a more severe SSc prognosis and skeletal muscle disease [3, 4], and it has been reported to play a role in inflammatory myopathy (IM) and in diabetic cardiomyopathy (DCM) [5, 6]. In DCM the phosphodiesterase type 5 inhibitor (PDE5i) sildenafil significantly decreased CXCL10 systemic and cellular release [7]. In SSc, sildenafil is used to treat pulmonary artery hypertension (PAH) and digital ulcers disease. Objectives: To determine the serum levels of CXCL10 in SSc patients with or without muscle involvement and treated or not with sildenafil. To determine the role of sildenafil on IFNγ+TNFα-induced CXCL10 release in human skeletal muscle cells (Hfsmc). Methods: Sera from 109 patients fulfilling ACR/EULAR 2013 classification criteria for SSc and 34 age and gender matched healthy controls (HC) were analysed by multiplexed, bead-based immunoassay. Hfsmc were cultured and analysed as previously described [5]. Results: CXCL10 serum level was significantly higher in SSc vs. HC (602.1±155.1 pg/ml vs 197.5±14.9 pg/ml, P<0.001) independently of diffuse or limited clinical subset (p>0.05); the presence of sildenafil in therapeutic regimen was associated with lower serum CXCL10 (455.2±211.8 pg/ml vs 633.1±183.02 pg/ml, P<0.05). CXCL10 was significantly higher in patients with increased Creatine Kinase (CK) (2703±2172 vs 454±82.51, P<0.01) and its concentration strongly correlated with the levels of CK (r=0.986, P<0.001) and with Medsger muscle Severity score (r=0.445, P<0.001). In vitro, sildenafil suppressed IFNγ+TNFα-induced CXCL10 release by Hfsmc in a dose dependent manner, down to 50% secretion at 1mM (P<0.05). The inhibition of CXCL10 secretion was associated with significant reduction in cytokine-induced STAT1, NFKB and JNK phosphorylation (P<0.01). Conclusions: High CXCL10 level is associated with SSc independently from local or diffuse clinical subset and is lower in patients assuming sildenafil independently of other therapies. The strong correlation of CXCL10 and severity of muscle damage as assessed by serum CK and Medsger Muscle severity score, strongly indicate/confirm the involvement of IFN-I pathway activation during myositis in SSc. The direct inhibitory effect of PDE5 inhibitor Sildenafil on proinflammatory induced CXCL10 secretion warrant further research on the potential role of PDE5 inhibitors as disease modifying agents in SSc. References: Varga J et al., J Clin Invest 2007, 117: 557–67. Higgs BW et al., Ann Rheum Dis 2011, 70:2029–36. Corrado A, Clin Ter 2014, 165:e436–41. Liu X et al., Arthritis Rheum 2013, 65:226–35. Crescioli C et al. Eur J Cell Biol. 2012, 91:139–49. Di Luigi L et al., PLoS One. 2013 Oct 30;8(10):e77745. Di Luigi et al., Inflammation 2016, 39(3):1238–52. Disclosure of Interest: None declared